Gallbladder perforation: An uncommon cause of peritonitis in a child. (November 2022) - Suleman, Mujaheed; Sadiq, Adnan; Amsi, Patrick; Lodhia, Jay
Abstract: Introduction and importance: Gallbladder perforations are infrequently encountered in the pediatric group but can be a cause of peritonitis with significant morbidity and mortality if not diagnosed and managed promptly. Case presentation: We present a case of a 10-year-old female who presented with peritonitis due to a perforated gallbladder diagnosed by CT-scan. She was managed surgically successfully. Clinical discussion: Gallbladder perforation due to cholecystitis is usually seen in the elderly population but is uncommon among the pediatric population. Mortality rate can be as high as 26 % hence early diagnosis is vital. Management is mostly surgical as seen in the index case. Conclusion: Clinicians should keep gallbladder perforation in mind as a differential diagnosis of acute abdomen in children although uncommon. Highlights: Gallbladder perforation is uncommon to the pediatric population. If encountered in children, causes significant morbidity and mortality Clinicians should keep it as a differential diagnosis of peritonitis with a high index of suspicion. Prompt management through surgery yields favourable outcome.